Utilization and Development of Libas (Spondias Pinnata) Spray-Dried Powder - Robelle M. Tapado (International Journal of Engineering and Management Research, 2023)
In this study, the effect of maltodextrin concentration on the physico-chemical, sensory and storage characteristics of Libas (Spondias pinnata) powder produced by spray drying was investigated. Initially, fresh Libas leaf extracts were drawn out in distilled water heated at 100°C for 30 minutes. 10, 20 and 30% maltodextrin was added to the solution prior to sieving. These solutions were then atomized in a pilot scale centrifugal spray dryer at an inlet temperature of 180°C, material cooling temperature of 70°C, fan operation frequency of 60 Hz, atomizer operation frequency of 300 Hz and mean outlet temperature of 125°C. Spray dried Libas leaf powder was analyzed for product yield, pH, moisture content, ash content and solubility time. The level of acceptability of the spray dried Libas leaf powder was also assessed in terms of appearance, taste, aroma, mouthfeel and overall acceptability using a 9-point hedonic scale conducted on thirty (30) sensory panelists. Findings of the study revealed that maltodextrin concentration significantly affected various physico-chemical, sensory and storage characteristics of spray dried Libas leaf powder. Product yield, solubility and residual moisture content were found to be significantly improved by an increase in maltodextrin concentration. However, it was also found that there is a decrease in the ash content and level of acceptability of the spray dried samples with an increase in maltodextrin concentration. Storage of the spray dried Libas leaf powder for six (6) months significantly affected pH and moisture content. No significant difference in sensory characteristics was detected among treatments indicating that powder quality is still acceptable during the six (6) months storage period.